Evaluation of Interventions for Individuals with Special Needs After an Earthquake: Teacher Perspective - KILIÇ, FİDAN GÜNEŞ GÜRGÖR; Tuna, D. Merve; Yurtçu, Ayşe Büşra Subaşı (Sakarya Üniversitesi Eğitim Bilimleri Enstitüsü, 2024)
Türkiye is in a geography where many large and small-scale earthquakes occur due to its location in the earthquake zone. The Kahramanmaraş earthquake on February 6, 2023, and the Hatay earthquake on February 20, 2023, affected individuals with special needs and their families as well as individuals with typical development. This research aims to determine the experiences of experts who meet/support individuals with special needs and their families in the earthquake zone or any province and their recommendations regarding future disasters. Therefore, focus group interviews were conducted with five special education teachers and a psychological counsellor. According to the results of the research, four themes were reached: the needs, the difficulties, the positive aspects of interventions for individuals with special needs after the earthquake and recommendations for a future earthquake. The results obtained from the findings of this study were discussed together with previous studies in the literature and suggestions were made regarding before, during and after disasters.
Keywords: Earthquake; Türkiye; Disability; Disaster; Teachers; Special Education Teacher; Focus Group Interview; Individuals with Special Needs